SYNTHESIS, CHARACTERIZATION AND ANTIMICROBIAL ACTIVITY OF SOME NOVEL 3,4-DISUBSTITUTED PYRAZOLE DERIVATIVES - GANESH AKULA; KAUSHAL K CHANDRUL; BHIKSHAPATHI DVRN (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The objective of the current work was to synthesize a series of 3,4-substituted pyrazoles from the cyclization of substituted aryl ethanone and hydrazine hydrate in a two-step process and screen the derivatives for their antimicrobial activity. Methods: The title compounds were derived from the condensation of ethanone intermediate with N, N-Dimethyl formamide-dimethyl acetal and hydrazine hydrate. Ethanone intermediate synthesized from substituted methyl phenylacetate in the presence of potassium t-butoxide with 6-methyl pyridine-2-carboxylic acid methyl ester. Results: The final products were characterized by detailed spectral analysis using Mass, Nuclear Magnetic Resonance, and Infra Red spectroscopy. All the compounds (4a-4j) showed significant antibacterial properties on both Gram-positive and Gram-negative bacteria. Interestingly, the selected microbes were found to be highly sensitive for compound 4a, 4c, 4d, 4h, and 4i. The molecules are also antifungal in nature, and they have a significant inhibitory effect on the growth of Candida albicans and Aspergillus niger. Conclusion: The results suggest that the developed derivatives bearing the pyrazole nucleus could be the lead structures for the development of antimicrobial agents for fatal infections.